2016
DOI: 10.5194/acp-16-6721-2016
|View full text |Cite
|
Sign up to set email alerts
|

Substantial secondary organic aerosol formation in a coniferous forest: observations of both day- and nighttime chemistry

Abstract: Abstract. Substantial biogenic secondary organic aerosol (BSOA) formation was investigated in a coniferous forest mountain region in Whistler, British Columbia. A largely biogenic aerosol growth episode was observed, providing a unique opportunity to investigate BSOA formation chemistry in a forested environment with limited influence from anthropogenic emissions. Positive matrix factorization of aerosol mass spectrometry (AMS) measurement identified two types of BSOA (BSOA-1 and BSOA-2), which were primarily … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 57 publications
6
46
0
Order By: Relevance
“…• Aerosol organic concentrations were enhanced by multiday accumulation of isoprene-related secondary particle mass • Three types of single-particle composition had mass fragments similar to three mass-weighted aerosol mass spectrometer composition factors • Isoprene-related organic aerosol mass fragments were mostly found on sulfate-containing particles, indicating selective uptake to particles characteristic fragment ion at m/z 91 (which we refer to as Factor91, also referred to as 91fac, OOA3, bSOA1, bSOA2, or Isoprene OA as noted in Table S4) Chen et al, 2015;Lee et al, 2016b;Robinson et al, 2011]. The consistent identification of these two factors in studies across North and South America as well as Europe indicates both the prevalence of bSOA worldwide and the general similarity of their composition (Table S4).…”
Section: Introductionmentioning
confidence: 93%
“…• Aerosol organic concentrations were enhanced by multiday accumulation of isoprene-related secondary particle mass • Three types of single-particle composition had mass fragments similar to three mass-weighted aerosol mass spectrometer composition factors • Isoprene-related organic aerosol mass fragments were mostly found on sulfate-containing particles, indicating selective uptake to particles characteristic fragment ion at m/z 91 (which we refer to as Factor91, also referred to as 91fac, OOA3, bSOA1, bSOA2, or Isoprene OA as noted in Table S4) Chen et al, 2015;Lee et al, 2016b;Robinson et al, 2011]. The consistent identification of these two factors in studies across North and South America as well as Europe indicates both the prevalence of bSOA worldwide and the general similarity of their composition (Table S4).…”
Section: Introductionmentioning
confidence: 93%
“…Lee et al (2008) suggested that in addition to weak condensation sinks, the presence of organic compounds could be one factor contributing to nighttime nucleation, together with lower temperatures. A possible explanation for the particle nucleation observed here at night is therefore the conversion of (semi) volatile organic compounds to less volatile water-soluble forms by reactions involving ozone or nitrate radicals (Lee et al, 2016;Alves et al, 2016). Brown et al (2006) suggested that an abundance of nitrogen and sulfur oxides in polluted atmospheres could lead to nighttime sulfuric acid production by reactions involving the NO 3 radical and SO 2 .…”
Section: Influence Of Relative Humiditymentioning
confidence: 85%
“…Finally, the reaction products are lost as the deposition of organic particles on various surfaces Holopainen et al 2017) or become oxidised to small-molecular gases such as CO or CO 2 (Kroll and Seinfeld 2008). Friedman and Farmer (2018) summarised the role of MT BVOCs in atmospheric reactions in the following three processes: (1) BVOCs acting as parent hydrocarbons for the formation of SOA in reactions with ozone (O 3 ) (Joutsensaari et al 2015;Zhao et al 2017;Berndt et al 2018), hydroxyl radical (OH) (Berndt et al 2018;Friedman and Farmer 2018) or nitrate (NO 3 ) radical ), (2) BVOCs that react with hydroxyl (OH) radicals to form peroxy radicals (RO 2 ) (Zhao et al 2015), which participate in photochemical tropospheric O 3 production (Berndt et al 2018;Friedman and Farmer 2018) and (3) BVOCs that react with O 3 at night to produce OH radicals (Lee et al 2016).…”
Section: Bvoc Reactions In the Atmospherementioning
confidence: 99%